48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-462
|View full text |Cite
|
Sign up to set email alerts
|

Validating BEM, Direct and Inverse Free Wake Models with the MEXICO Experiment.

Abstract: The primary objective of the MEXICO (Model Experiments in Controlled Conditions) project was to generate experimental data for validation of models for wind turbines. Kulite c pressure sensors were used for pressure measurements while Particle Image Velocimetry was used with the aim of tracking the tip vortex trajectory. The pressure measurements were carried out for both axial and yawed flow conditions with yaw angles of 15 o , 30 o and 45 o . For the Particle Image Velocimetry measurements data was gathered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The next generation of wind turbine aerodynamic analysis tools—computational fluid dynamics and free vortex models— may improve the simulation of complex aerodynamic operating conditions. However, these techniques are predominantly used as research tools.…”
Section: Introductionmentioning
confidence: 99%
“…The next generation of wind turbine aerodynamic analysis tools—computational fluid dynamics and free vortex models— may improve the simulation of complex aerodynamic operating conditions. However, these techniques are predominantly used as research tools.…”
Section: Introductionmentioning
confidence: 99%
“…BEM theory can be considered simple, and it has been derived several decades ago; but still, it is used in present days, mostly but not only in preliminary stages of HAWT design. Other more complex approaches include actuator line theory and vortex wake theory, both computationally very consuming. Actuator line theory solves full 3D Reynolds Averaged Navier–Stokes equations around the HAWT rotor and introduces the rotating blade forces contribution through source terms along lines representing the blades.…”
Section: Methodsmentioning
confidence: 99%
“…In the NREL Phase VI rotor experiment, 43,52 sectional angles of attack were measured at five spanwise stations by means of five-hole probes mounted ahead of the blade leading edge. These served as data for a later development of an inverse free-wake lifting line model 53,54 that produced both accurate and consistent angle-of-attack data for both the NREL Phase VI and MEXICO experiments, see also Schreck et al 47 Computed angles of attack shown in Figure 10 were extracted directly from the computations over the range of wind speeds shown in Figure 9. At the 30% radial station in Figure 10(a), a large amount of correction to the normal force coefficient is apparent for the SBSD when compared with the 2D polar data.…”
Section: Nrel Phase VI Rotor-power Curvementioning
confidence: 99%